General Jonas Žemaitis’s Contribution to the Partisan War in Lithuania - Žemaitienė, Nijolė (Genocidas ir rezistencija, 1998)
This article presents the biography of partisan leader Jonas Žemaitis, his role and importance in the partisan movement.
Keywords: armed resistance; partisans; Jonas Žemaitis; leaders of partisans